It's a two way street : striking the balance between routinisation and responsiveness in emergency calls. - Neel, Sheryl (My University, 2014)
A call taker is the first point of contact in the emergency service system and thus the interface between the caller and ambulance dispatch. Misunderstandings in an emergency call have implications for the survival of patients. Using an applied conversation analytic approach this study examined participants’ use of conversational repair as an interactional strategy. Data included 101 calls from a South African emergency medical services call centre. The data set was comprised of two distinct subsets, namely: the 107 and public corpora. The 107 corpus (53 calls) contained calls from a general emergency call centre. The 107 caller thus served as a mediating party on behalf of the public caller. The public corpus (48 calls) comprised calls received directly from members of the public. The data subsets afforded a unique opportunity to analyse ways in which participants to an emergency call manage asymmetries of knowledge. Differential patterns of the type and purpose of repair were tracked across both data sets and similarities and differences were explored. Both data sets showed that participants’ choice of interactional strategies was customized based on an ongoing assessment of knowledge asymmetries. However, whilst knowledge asymmetries posed some constraints an overriding interactional constraint, inherent within the institutional nature of the emergency call, was a rigid adherence to routinized protocols. The call taker’s dilemma was thus identified as the management of these constraints through the frequent use of conversational repair. Although a level of responsiveness is required to glean quality information from callers, high volumes of emergency calls would not be possible without routinized protocols. However, increased orientation to routinized protocols led to a decreased orientation to responsiveness. This research therefore showed that knowledge symmetry is not necessarily more advantageous but that successful call trajectory is reliant on the call taker’s ability to maximize the collaborative nature of the interaction and effectively negotiate through the judicious use of repair and other relevant interactional strategies. This has important implications for call taker training.
Keywords: Emergency medical services--South Africa.; Emergency communication systems--South Africa.; Telephone--South Africa--Emergency reporting systems.; Emergency management--Employees--Training of--South Africa.